Peran Media Pembelajaran Flashcard Berbasis Augmented Reality Terhadap Kemampuan Berpikir Peserta Didik: Systematic Literature Review - Syahnur Rohim; As Elly; Yufitri Yanto (Proceeding of Silampari Conference of Life Science and Technology, 2026)
The integration of Augmented Reality (AR) into educational media has attracted increasing attention due to its potential to foster students' thinking skills through interactive and immersive learning experiences. This study aims to systematically review the role of AR-based flashcard learning media in improving students' thinking skills, identify the forms and characteristics of the media, and examine the challenges and opportunities associated with its implementation. The study employed a Systematic Literature Review (SLR) using the PRISMA protocol. A total of 196 articles were initially identified through the Publish or Perish database, and after a rigorous screening process, 10 peer-reviewed journal articles published between 2023 and 2026 met the inclusion criteria. The findings indicate that AR-based flashcards positively influence students' critical thinking and problem-solving skills by providing interactive three-dimensional visualization, real-time feedback, and contextual learning experiences. Most studies developed AR flashcards using Research and Development methods and reported that the media were valid, practical, and effective for classroom implementation. However, challenges remain, including limited technological infrastructure, teachers' digital competence, and the restricted application of AR across educational levels and subject areas. Overall, AR-based flashcards represent a promising instructional innovation that can enhance students' thinking skills and support technology-enhanced learning in the digital era.